The peacock manoeuvre: Ethnographic research on group behaviour among Danish ultras groups. (1st March 2017) - Laursen, Rasmus Beedholm
Most contemporary research on Danish football fandom has been conducted on hooliganism while research in other fan groups such as ultras is scarce. Although, some Danish ultras groups socialize with and occasionally engage in conflicts, this article suggests that ultras activities differ markedly from hooliganism despite that both fan segments is entitled 'risk fans'. Based on a longitudinal three-year ongoing ethnography study of Danish ultras groups this article shows that ultras group members in certain situations instantly can change attitude from calm and peaceful to aggressive and confrontational. However, this article also illustrates that this transformation of behaviour rarely, if ever, escalates into psychical violence. Inspired by Erving Goffman's theatrical theory, this article suggests that such aggressive ultras group behaviour is a performative act that primarily serves to intimidate or scare off rivals; rather than a genuine desire for demonstrating violent behaviour. To capture this performativity, this article uses the analogy of the peacock, which 'puff itself up' as a strategic manoeuvre to intimidate rivals and thereby avoid a physical confrontation. It is in this sense that the analogy is applied. Subsequently, this article 'maps out' the two typical social occasions where the manoeuvre unfolds.